Agro-industrial by-products as substrates for the production of bacterial protease and antioxidant hydrolysates. (October 2021) - Clerici, Naiara Jacinta; Lermen, Andréia Monique; Daroit, Daniel Joner
Abstract: Feather meal (FM), sweet whey (LW), lyophilized whey (WL), and cassava bagasse (CB) were investigated as substrates to obtain extracellular proteases and bioactive hydrolysates during cultivations with Bacillus sp. CL33A. Initial evaluations indicated that FM (10 g/L), as single substrate, resulted in higher protease production, and higher soluble protein contents and antioxidant activities in culture supernatants, in comparison to LW, WL (5, 10, 15 g/L) or CB (5, 10, 15 g/L plus 1 g/L (NH4 )2 SO4 )). Increasing FM to 30 g/L enhanced protease production 6-fold, which peaked after 4 days of cultivation. Protease production was paralleled by increases in soluble protein content in supernatants, which demonstrated radical-scavenging, Fe 3+ -reducing, and Fe 2+ -chelating activities. Supplementation of 30 g/L FM with 5 g/L WL increased protease yields (1.8-fold) after 4 days; enzyme production peaked after 6 days of cultivation, corresponding to a 3-fold increase in comparison to FM-only medium at day 4. Adding CB (5 and 10 g/L) to 30 g/L FM increased protease production by 110–130% after 4 days of cultivation. LW-supplemented FM medium showed decreased protease production, postponing soluble protein release and increases on antioxidant activities. No marked influences of supplemental WL or CB were observed on the antioxidant activities of obtained protein hydrolysates. FM is a low-cost substrate to simultaneously obtain bioproducts. The use of WL or CB as co-substrates might be interesting to manage and add value to these by-products. The obtained protease might find applications in the enzymatic hydrolysis of food proteins, and antioxidant hydrolysates deserve investigations as animal feed. Highlights: Co-production of bacterial protease and antioxidant protein hydrolysates. FM as a better substrate to obtain bioproducts through submerged cultivations. Supplementation of FM with WL or CB increased protease production. No prominent influence of WL and CB on antioxidant activities of FM hydrolysates. Valorization of agro-industrial by-products and problematic waste streams.